Globalization, Financial Markets, and Fiscal Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines how fiscal policy can contribute to realizing the benefits of two important ongoing developments, globalization and financial deepening.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet